Determinasi Kepuasan Kerja Karyawan: Pengaruh Lingkungan Kerja dan Disiplin Kerja pada CV. Dynasty Group - Theodorus Kristianto; Salfin Tandidatu; Mince Anggreyani (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the effect of work environment and work discipline on employee job satisfaction at CV. Dynasty Group in Tarakan City. The study employed a quantitative approach using a survey method involving 37 employees as the sample. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that work environment and work discipline have a positive and significant effect on job satisfaction, both partially and simultaneously. Work discipline is identified as the most dominant variable influencing job satisfaction. Simultaneously, both variables have a very strong effect, contributing 81.9% to explaining the variation in employee job satisfaction. These findings suggest that improving the quality of the work environment and implementing effective work discipline are essential factors in enhancing employee job satisfaction.